Safety and feasibility of Myomectomy during cesarean delivery - Bhattachan, Kabin; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema Kumar; Shrestha, Ranjana (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To assess the safety and feasibility of myomectomy during cesarean delivery. Methods: This was a retrospective descriptive study conducted at Kathmandu Model Hospital. Data on cesarean myomectomy were obtained from hospital records and analyzed in terms of demographic profile, number, size and location of fibroids, intraoperative blood loss, and drop in hemoglobin level, blood transfusion, birthweight and duration of hospital stay.Results: Mean age of mother and gestational age at delivery were 32.6 years and 37.8 weeks respectively. Seventeen cases (58.6%) had multiple fibroids. Seventeen (58.6%) of the fibroids were intramural, 10 (34.4%) sub serosal and 2(6.8%) were submucosal. Nine cases (31.1%) had intraoperative blood loss of 500ml to 1000ml with mean loss of 420 ml. Only One case who had blood loss of 1500ml due to presence of fibroid in lower segment of uterus required 3 unit of blood transfusion. The mean preoperative & postoperative hemoglobin were 12.23 gm/dl and 11.25gm/dl. The mean birthweight & duration of hospital stay were 2.8 kg and 2.3 days.Conclusion: Cesarean myomectomy is a safe and feasible procedure.Keywords: cesarean, myomectomy, safety